Sphingobium sp. V4, a bacterium degrading multiple allelochemical phenolic acids - Chunyang Zhang; Shuping Liu; Qingying Guo; Demin Li; Zelin Li; Qinyuan Ma; Hong Liu; Qian Zhao; Hongliang Liu; Zhongfeng Ding; Weihua Gong; Yuhao Gao (Annals of Microbiology, 2024)
Abstract Background Continuous cropping challenges constrain the development of agriculture. Three main obstacles limit continuous cropping: autotoxicity of plant allelochemicals, deterioration of physicochemical characteristics of soil, and microflora imbalance. Plant-derived phenolic acids can cause autotoxicity, which is considered the main factor mediating continuous cropping obstacles. Reducing the phenolic acids in continuous cropping soils can decrease the autotoxicity of phenolic acids and ameliorate continuous cropping obstacles. Therefore, it is important to study the microbial resources that degrade allelochemical phenolic acids. Thus, the bacterial strain V4 that can degrade phenolic acids was isolated, identified, and genomically analyzed. Results Strain V4 isolated from strawberry soil using vanillic acid-mineral agar was identified as a Gram-negative short rod bacterium. Subsequent 16S rRNA phylogenetic analysis revealed that V4 clustered with members of the genus Sphingobium. The most closely related species were Sphingobium lactosutens DS20T (99% similarity) and Sphingobium abikonense NBRC 16140T (97.5% similarity). V4 also shared > 95% sequence similarity with other members of Sphingobium, so Sphingobium sp. V4 was named accordingly. Biochemical tests revealed that the biochemical characteristics of Sphingobium sp. V4 were similar to its most similar strains except for some properties. Sphingobium sp. V4 effectively degraded vanillic acid, ferulic acid, p-coumaric acid, p-hydroxybenzoic acid, and syringic acid. V4 grew best at the conditions of 30 °C, pH 6.0–7.0, and 0–0.05% NaCl. 500 mg/L vanillic acid was completely degraded by V4 within 24 h under the optimal conditions. Whole genome analysis showed that Sphingobium sp. V4 contained one chromosome and three plasmids. Two genes involved in vanillic acid degradation were found in the V4 genome: the gene encoding vanillate O-demethylase oxidoreductase VanB on the chromosome and the gene encoding vanillate monooxygenase on a large plasmid. The organization of vanillate catabolic genes differed from the adjacent organization of the genes, encoding vanillate o-demethylase VanA and VanB subunits, in Pseudomonas and Acinetobacter. Conclusions The isolated bacterium Sphingobium sp. V4 degraded multiple phenolic acids. Its properties and genome were further analyzed. The study provides support for further investigation and application of this phenolic acid-degrading microorganism to alleviate continuous cropping obstacles in agriculture.